A Counseling on Complementary Food to Mothers of Infants Aged 6–24 Months at A Community Clinic in Sukmajaya - Avliya Quratul Marjan; A’immatul Fauziyah; M. Ikhsan Amar (Institute for Research and Community Services, 2019)
MPASI, complementary food to breast milk, is food or drink containing nutrients, given to babies or infants aged 6-24 months, and given in stages according to the age and digestive capacity of the babies or infants to meet their nutritional needs other than breast milk. The objective of the activity was to improve the mothers’ knowledge of correct and good complementary food for their under-five-year-old infants in Sukmajaya, Depok 2018 and to determine the differences of these mothers’ knowledge about how to process and use ingredients for the complementary food before and after counseling. The method of this community service activity was through pre- and post-test designs. The results showed that the average score of mothers; knowledge before the counseling was 73.00 and after the counseling 79.43. The difference in the mean value between the first and second measurements was 6.43 and the results of the statistical test show the value of P value <0.05. Therefore, it can be concluded that there were significant differences between the pre-test (before counseling) and post-test (after counseling) scores. Based on the results of data processing and analysis, it was found that 66.66% of respondents experienced improving knowledge of complementary food, although the number was still below the target of 70%.